P603 Persistence of vedolizumab maintenance therapy: Findings from a Belgian registry. (15th January 2020) - Louis, E; Muls, V; Bossuyt, P; Colard, A; Nakad, A; Baert, D; Mana, F; Caenepeel, P; Vanden Branden, S; Vermeire, S; D'Heygere, F; Strubbe, B; et al.
Abstract: Background: Clinical trials and observational studies have demonstrated the clinical efficacy of vedolizumab (VDZ) as maintenance therapy for Crohn's disease (CD) and ulcerative colitis (UC). This report presents long-term data on persistence of VDZ maintenance therapy in real-world clinical practice in Belgium. Methods: The Belgian VDZ Registry (ENCePP EUPAS6469) enrolled 202 VDZ-treated ulcerative colitis (UC) or Crohn's disease (CD) adult patients (26% with no prior use of anti-TNF therapy) from 19 centres across Belgium. The median length of VDZ therapy prior to enrolment was 11 months. Patients were followed-up every 6 months after enrolment with the assessment of IBD features, use of biologics, and disease activity. Clinical remission was defined as the Harvey–Bradshaw Index (HBI) <5 or partial Mayo Score (pMS) <2. Missing value imputation (last observation carried forward) was used to partially account for missing disease activity scores. If a 6-monthly disease activity score was missing, the disease activity score from the previous 6-monthly assessment was used. Results: The mean duration of VDZ therapy, including use prior to enrolment, was 31 months, with 68% of CD patients and 75% of UC patients using VDZ therapy for 48 months. Clinical remission rate after 42 months of VDZ therapy was higher in UC (84%) than CD (67%), and higher for patients without prior anti-TNF therapy (87%) than those with prior anti-TNF therapy (70%). Fifty-seven (29.4%) patients discontinued VDZ during follow-up, due to loss of response ( n = 40), adverse event ( n = 7), clinical remission ( n = 4), pregnancy planning ( n = 3), and patient choice ( n = 3). Conclusion: These real-world long-term Belgian data demonstrate a high persistence of VDZ maintenance therapy among both CD and UC patients, with highest clinical remission rates seen in patients with UC and those with no prior anti-TNF therapy.